Talent identification and development of youth fencers: coaches’ perspectives - Hayder N. Jawoosh; Lim Hooi Lian; Rahimi Che Aman (International Journal of Evaluation and Research in Education (IJERE), 2026)
Talent identification (TID) in sports has been found to be heavily influenced by the expertise and judgment of the coach. However, the factors that inform this judgment have been found to be complex and understudied, especially in the sport of fencing. Inconsistencies have also been found in the concept and construct of TID in the development programs of young athletes. Therefore, the purpose of this study was to identify the essential criteria that inform TID in young male fencers aged between 12 and 15 years and to describe the criteria in the selection of young athletes to a fencing club. A qualitative research methodology was employed in this study. In this research, six male coaches from professional clubs affiliated with the Iraqi Fencing Federation were interviewed. The results of this study revealed that technical, tactical, and mental factors, especially fencing ability, decision-making capacity, and intrinsic motivational factors, were found to be essential in TID. Physiological, physical, and anthropometric factors were also found to be of little importance in TID. In conclusion, TID in young fencers needs to be informed by a holistic approach that considers different dimensions of development. Further research in this area needs to be conducted to refine the criteria in TID.